Polygyny : what it means when African American Muslim women share their husbands - Majeed, Debra (Gainesville : University Press of Florida, 2015)
Debra Majeed's ethnography of contemporary African American Muslim polygyny illuminates the varieties of and struggles within a type of family whose form and function is contrary to U.S. civil law.
The road to understanding polygyny -- Agency and authority in polygyny -- Religious and experiential prescriptions -- Legalities and emotional well-being -- Imam Mohammed's commentary on polygyny -- Mental health and living polygyny -- Afterword: Muslim womanist praxis and polygyny.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Polygyny -- United States; African American women -- United States; Muslim women -- United States; Man-woman relationships -- United States; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Popular Culture; African American women; Man-woman relationships; Muslim women; Polygyny; United States; RELIGION / Islam / General; Electronic books